Health‐related quality of life in children and adolescents with pleuropulmonary blastoma: A report from the International PPB/DICER1 Registry. Issue 4 (24th November 2022) - Nelson, Alexander T.; Dybvik, Anna; Mallinger, Paige; Weiss McQuaid, Shelly; Watson, Dave; Harney, Laura A.; Stewart, Douglas R.; Dehner, Louis P.; Messinger, Yoav H.; Kunin‐Batson, Alicia S.; Schultz, Kris Ann P.
Abstract: Purpose: Pleuropulmonary blastoma (PPB) is the most common lung cancer of infancy and early childhood and is associated with germline DICER1 variants. Type I and Ir PPB are cystic lesions treated surgically, with a subset of children with type I receiving chemotherapy. Type II and III are more aggressive lesions, treated with surgery, intensive chemotherapy and potentially radiation. We sought to assess health‐related quality of life (HRQoL) in children with PPB and known germline DICER1 variants. Methods: Children with a diagnosis of PPB or germline DICER1 pathogenic variant without history of PPB or other DICER1 ‐related neoplasm ( DICER1 + only) were enrolled in the International PPB/ DICER1 Registry. Parent reports for participants aged 2–17 years for the PedsQL v.4 and PedsQL Multidimensional Fatigue Scale v.3 were collected. Fatigue, physical, and psychosocial function scores were compared. Results: Analysis included 84 participants (PPB type Ir = 20, type I = 15, type II/III = 27, DICER1 + only = 22). Total fatigue scores of participants with type I and II/III PPB were lower compared to DICER1 + only, with effect size larger in type II/III (−0.82 vs. −0.40). Total psychosocial and physical functioning scores were lower in participants with type I and type II/III PPB compared to DICER1 + only, with larger effects noted in type II/III. Female sex was suggestive of worse HRQoL for both type I/Ir and type II/III cohorts. Conclusions: These data demonstrate the importance of regular HRQoL assessment in patients with a history of PPB as well as the importance and feasibility of studying HRQoL in children with rare tumors.